2015
DOI: 10.1021/jacs.5b00535
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Identification of an FeIII Center, not FeIV, in the Crystalline Sc–O–Fe Adduct Derived from [FeIV(O)(TMC)]2+

Abstract: The apparent Sc3+ adduct of [FeIV(O)-(TMC)]2+ (1, TMC = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane) has been synthesized in amounts sufficient to allow its characterization by various spectroscopic techniques. Contrary to the earlier assignment of a +4 oxidation state for the iron center of 1, we establish that 1 has a high-spin iron(III) center based on its Mössbauer and EPR spectra and its quantitative reduction by 1 equiv of ferrocene to [FeII(TMC)]2+. Thus, 1 is best described as a ScIII–O–FeII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 30 publications
6
69
0
Order By: Relevance
“…In addition to biological oxidations, redox-inactive metal ions are also frequently employed to improve the stability and/or to modulate the reactivity of transition metal catalysts in heterogeneous oxidations. 6 Nam and Fukuzumi reported that Lewis acid like Sc 3+ can substantially accelerate the electron transfer rate from a series of one-electron reductants to a nonheme oxoiron(IV), Fe IV (N4Py)(O), 7 and similar acceleration effect was also observed in oxidative dimerization and Ndemethylation of N,N-dimethylaniline. Different from the complicated biological and heterogeneous systems, homogeneous system can offer simpler models to help understanding how these redox-inactive metal ions participate in the oxidation events and affect the reactivity properties of redox-active metal ions.…”
Section: Introductionmentioning
confidence: 76%
“…In addition to biological oxidations, redox-inactive metal ions are also frequently employed to improve the stability and/or to modulate the reactivity of transition metal catalysts in heterogeneous oxidations. 6 Nam and Fukuzumi reported that Lewis acid like Sc 3+ can substantially accelerate the electron transfer rate from a series of one-electron reductants to a nonheme oxoiron(IV), Fe IV (N4Py)(O), 7 and similar acceleration effect was also observed in oxidative dimerization and Ndemethylation of N,N-dimethylaniline. Different from the complicated biological and heterogeneous systems, homogeneous system can offer simpler models to help understanding how these redox-inactive metal ions participate in the oxidation events and affect the reactivity properties of redox-active metal ions.…”
Section: Introductionmentioning
confidence: 76%
“…More interestingly, the isomer shift found for 2 is halfway between the values for 1 and 3 . 9 However, the magnitude of the coupling constant J cannot be reliably determined, because Mössbauer measurements at higher temperature (up to 180 K) and high applied fields (up to 7 T) show that the electronic systems of these compounds still exhibit intermediate magnetic relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, 3 has an Fe⋯Ce distance of 3.825(5) Å, which is longer than those found for other Fe III –O–M complexes, e.g. ≤ 3.61 Å for M = Fe III , [9b],[14] and 3.64 for M = Sc III , [8] reflecting the larger ionic radius of the Ce IV center.…”
mentioning
confidence: 82%